Stakeholder Management in Public Sector Infrastructure Projects - Waris, Muhammad (2022)
The underlying risks and complexities in government infrastructure projects have increased the importance of external stakeholder management in contemporary project management. In developing countries, it is also important for policymaking and planning of infrastructure programs due to the varying nature of stakeholders and their expectations from the government. Few studies have looked at how external stakeholders are involved in public infrastructure projects and how they work together to achieve common project goals by overcoming communication and decision-making barriers. The internal stakeholders and project managers also need to properly liaise with the external stakeholders without compromising the project goals. Thus, there is a need to strategize the stakeholder management process to improve public sector infrastructure projects, especially from a developing nation's perspective. Therefore, the scope of this research has evaluated the prevalence of external stakeholder management in public sector infrastructure construction projects in Pakistan by developing and validating its five core dimensions. Among the constructs were identification and classification, communication, engagement, empowerment, and risk control. Besides this, twenty-seven sub-variables of stakeholder management have also been identified in the context of public sector projects. The results of the factor loading show that "Risk Control" is the most contributing dimension of stakeholder management, and "Empowerment" is the least concern in the current practices. The study emphasizes the importance of establishing a systematic and comprehensive framework for empowering external stakeholders, which will strengthen and improve performance and project outcomes. This study reveals insights that will assist project organizations in integrating external stakeholders into their government-sponsored projects with their effective empowerment and sufficient engagement.